Antitumor Effects of CD40 Ligand‐Expressing Endothelial Progenitor Cells Derived From Human Induced Pluripotent Stem Cells in a Metastatic Breast Cancer Model. (27th June 2014) - Purwanti, Yovita Ida; Chen, Can; Lam, Dang Hoang; Wu, Chunxiao; Zeng, Jieming; Fan, Weimin; Wang, Shu
Abstract : Endothelial progenitor cells (EPCs) are attractive as cellular vehicles for targeted cancer gene therapy. An embryoid body formation method was used to derive CD133 + CD34 + EPCs from human induced pluripotent stem (iPS) cells. The findings suggest that human iPS cell‐derived EPCs have the potential to serve as tumor‐targeted cellular vehicles for anticancer gene therapy. Abstract : Given their intrinsic ability to home to tumor sites, endothelial progenitor cells (EPCs) are attractive as cellular vehicles for targeted cancer gene therapy. However, collecting sufficient EPCs is one of the challenging issues critical for effective clinical translation of this new approach. In this study, we sought to explore whether human induced pluripotent stem (iPS) cells could be used as a reliable and accessible cell source to generate human EPCs suitable for cancer treatment. We used an embryoid body formation method to derive CD133 + CD34 + EPCs from human iPS cells. The generated EPCs expressed endothelial markers such as CD31, Flk1, and vascular endothelial‐cadherin without expression of the CD45 hematopoietic marker. After intravenous injection, the iPS cell‐derived EPCs migrated toward orthotopic and lung metastatic tumors in the mouse 4T1 breast cancer model but did not promote tumor growth and metastasis. To investigate their therapeutic potential, the EPCs were transduced with baculovirus encoding the potent T cell costimulatory molecule CD40 ligand. The systemic injection of the CD40 ligand‐expressing EPCs stimulated the secretion of both tumor necrosis factor‐α and interferon‐γ and increased the caspase 3/7 activity in the lungs with metastatic tumors, leading to prolonged survival of the tumor bearing mice. Therefore, our findings suggest that human iPS cell‐derived EPCs have the potential to serve as tumor‐targeted cellular vehicles for anticancer gene therapy.